Distinct Hypothalamic Neurons Mediate Estrogenic Effects on Energy Homeostasis and Reproduction - Xu, Yong (2011)
Estrogens regulate body weight and reproduction primarily through actions on estrogen receptor-α (ERα). However, ERα-expressing cells mediating these effects are not identified. We demonstrate that brain-specific deletion of ERα in female mice causes abdominal obesity stemming from both hyperphagia and hypometabolism. Hypometabolism and abdominal obesity, but not hyperphagia, are recapitulated in female mice lacking ERα in hypothalamic steroidogenic factor-1 (SF1) neurons. In contrast, deletion of ERα in hypothalamic pro-opiomelanocortin (POMC) neurons leads to hyperphagia, without directly influencing energy expenditure or fat distribution. Further, simultaneous deletion of ERα from both SF1 and POMC neurons causes hypometabolism, hyperphagia and increased visceral adiposity. Additionally, female mice lacking ERα in SF1 neurons develop anovulation and infertility, while POMC-specific deletion of ERα inhibits negative feedback regulation of estrogens and impairs fertility in females. These results indicate that estrogens act on distinct hypothalamic ERα neurons to regulate different aspects of energy homeostasis and reproduction.